Multilevel Analysis on the Biological, Social Economic, and Environmental Factors on the Risk of Pneumonia in Children Under Five in Klaten, Central Java - Nurul Ulya Luthfiyana; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2018)
Background: Pneumonia is one of the leading causes of death in children under five in the world, particularly in the developing countries including Indonesia. Imbalance between host, agent, and environment, can cause the incidence of pneumonia. This study aimed to examine the biological, social economic, and environmental factors on the risk of pneumonia in children under five using multilevel analysis with village as a contextual factor.Subjects and Method: This was an analytic observational study with case control design. The study was conducted in Klaten District, Central Java, from October to November, 2017. A total sample of 200 children under five was selected for this study by fixed disease sampling. The dependent variable was pneumonia. The independent variables were birth weight, exclusive breastfeeding, nutritional status, immunization status, maternal education, family income, quality of house, indoor smoke exposure, and cigarette smoke exposure. The data were collected by questionnaire and checklist. The data were analyzed by multilevel logistic regression analysis.Results: Birth weight ≥2.500 g (OR=0.13; 95% CI= 0.02 to 0.77; p= 0.025), exclusive breastfeeding (OR= 0.15; 95% CI= 0.02 to 0.89; p= 0.037), good nutritional status (OR=0.20; 95% CI= 0.04 to 0.91; p= 0.038), immunizational status (OR= 0.12; 95% CI= 0.02 to 0.67; p= 0.015), maternal educational status (OR= 0.18; 95% CI= 0.03 to 0.83; p= 0.028), high family income (OR= 0.25; 95% CI= 0.07 to 0.87; p= 0.030), and good quality of house (OR= 0.21; 95% CI= 0.05 to 0.91; p= 0.037) were associated with decreased risk of pneumonia. High indoor smoke exposure (OR= 8.29; 95% CI= 1.49 to 46.03; p= 0.016) and high cigarette smoke exposure (OR=6.37; 95% CI= 1.27 to 32.01; p= 0.024) were associated with increased risk of pneumonia. ICC= 36.10% indicating sizeable of village as a contextual factor. LR Test p= 0.036 indicating the importance of multilevel model in this logistic regression analysis.Conclusion: Birth weight, exclusive breastfeeding, good nutritional status, immunizational status, maternal educational status, high family income, and good quality of house decrease risk of pneumonia. High indoor smoke exposure and high cigarette smoke exposure increase risk of pneumonia.Keyword: pneumonia, biological, social economic, environmental factor, children under fiveCorrespondence: Nurul Ulya Luthfiyana, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: ulya.luthfiyana@gmail.com.Journal of Epidemiology and Public Health (2018), 3(2): 128-142https://doi.org/10.26911/jepublichealth.2018.03.02.03